Effect of elderly fitness exercise combined with Surya Namaskar Yoga on the youngest and middle old’ body mass index and physical fitness - Desy Yunita Utami; Sumaryanti Sumaryanti; Novita Intan Arovah; Ali Satia Graha; Wawan Sundawan Suherman; Febriansyah Hendra Lukmana Putra (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
The purpose of this study was to analyze the effect of a combination of fitness exercise for the elderly and Suryanamaskar yoga on body mass index and physical fitness of youngest and middle old in Mojolaban District. This research is a quasi-experimental research with one group pretest-posttest design. The research population is the elderly in Mojolaban District. Sampling was done by purposive sampling from 42 elderly integrated healthcare center members. All samples followed the treatment with a frequency of 4x/week for 24 meetings, light intensity (DN elderly 96-112x/minute), 35 minutes. Then measured BMI with the formula Weight (kg)/Height (m2) and physical fitness was measured by the senior fitness test. Normality test using Shapiro Wilk followed by Wilcoxon Signed Rank test. The results of the study based on the Wilcoxon Signed Rank test for the youngest old, the pre-test value of 24.1538 ± SD 4.75014 decreased to 23.8381 ± SD 4.69895 in the post-test with a p-value of 0.01 in the BMI variable. The pre-test value of 10.05 ± SD 1.287 increased to 10.79 ± SD 1.554 in the post-test with a p-value of 0.001 on the physical fitness value variable. The results of the Wilcoxon Signed Rank test for the middle old obtained a p-value of 0.012 for the BMI variable and a p-value of 0.046 for the physical fitness value variable. It can be concluded that there is a decrease in the BMI of the youngest and middle old, as well as an increase in the physical fitness value of the youngest and middle old.